2005
DOI: 10.1002/bit.20676
|View full text |Cite
|
Sign up to set email alerts
|

E‐cadherin synergistically induces hepatospecific phenotype and maturation of embryonic stem cells in conjunction with hepatotrophic factors

Abstract: Since effective cell sourcing is a major challenge for the therapeutic management of liver disease and liver failure, embryonic stem (ES) cells are being widely investigated as a promising source of hepatic-like cells with their proliferative and pluripotent capacities. Cellcell interactions are crucial in embryonic development modulating adhesive and signaling functions; specifically, the cell-cell adhesion ligand, cadherin is instrumental in gastrulation and hepatic morphogenesis. Inspired by the role of cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 94 publications
0
35
0
Order By: Relevance
“…However we do see E-cadherin production later on in the differentiation process, Figure 2A. The E-cadherin protein itself has been identified within liver tissue samples, (Figarella-Branger et al, 1995) and has been reported to play a role in hepatic differentiation, (Brieva and Moghe, 2004;Dasgupta et al, 2005). Furthermore, the presence of tight junctions facilitated by the presence of E-cadherin, are necessary for normal liver function.…”
Section: Discussionmentioning
confidence: 82%
“…However we do see E-cadherin production later on in the differentiation process, Figure 2A. The E-cadherin protein itself has been identified within liver tissue samples, (Figarella-Branger et al, 1995) and has been reported to play a role in hepatic differentiation, (Brieva and Moghe, 2004;Dasgupta et al, 2005). Furthermore, the presence of tight junctions facilitated by the presence of E-cadherin, are necessary for normal liver function.…”
Section: Discussionmentioning
confidence: 82%
“…49 Similarly, mouse ESCs grown as EBs overexpressing E-cadherin were shown to have higher transcript levels of G6pc in response to growth factor cocktails than EBs in which E-cadherin expression was downregulated. 50 Other than cell-cell interactions, polarization of cells in 3D configurations has been shown to help in enhancing and stabilizing the differentiated functions of hepatoyctes. 47,51 Whether similar positive effects of 3D culture on hepatocytes are in play in enhancing differentiation of stem cell certainly requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The basic idea behind the EB protocol is to mimic the process of embryonic development [13]. Most cell lineages, including the neuronal, mesoderm and hepatocyte lineages have been shown to be generated within the EB [32][33][34]. However, the structure of the EB is far more heterogeneous than the actual embryo.…”
Section: Current Protocols Of Es Cell Culturementioning
confidence: 99%